Water-resistant hot melt film of waterproof roll and preparation method of water-resistant hot melt film

By optimizing the composition and preparation parameters of the hot melt film of the waterproof coil, the problems of weak tensile strength and poor waterproofing effect are solved, and higher waterproof performance, ultraviolet resistance, heat resistance and elongation are achieved, and the service life of the waterproof coil is extended.

CN119735882AInactive Publication Date: 2025-04-01BEIXIN WATERPROOF (XIANYANG) CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411957984.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-01
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The hot melt film of existing waterproof coils has weak tensile strength and poor waterproofing effect, resulting in a short service life.

Method used

By controlling the dosage and preparation parameters of polyolefin elastomer POE and modification enhancer, the tensile strength of the hot melt film is improved; by controlling the dosage and preparation parameters of homemade water barriers and modified silane coupling agents, the waterproofing effect of the hot melt film is improved; by changing the dosage and preparation parameters of the modified silane coupling agents and modified phenolic resins, the UV resistance and heat resistance of the hot melt film is improved; by controlling the dosage and mixing process parameters of the composite antioxidant, the elongation of the hot melt film is improved.

Benefits of technology

The tensile strength, waterproof effect, ultraviolet resistance, heat resistance and elongation of the hot melt film are significantly improved, thereby extending the service life of the waterproof coil material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735882A_ABST
    Figure CN119735882A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, in particular to a water-resistant hot melt film of a waterproof roll and a preparation method of the water-resistant hot melt film. The problem that the waterproof roll is short in service life is solved. Synthetic raw materials of the water-resistant hot melt film comprise a polyolefin elastomer POE, a self-made water-resistant agent, a modified reinforcing agent, a modified silane coupling agent, improved phenolic resin and a composite antioxidant. The tensile strength of the hot melt film is improved by controlling the dosage of the polyolefin elastomer POE and synthesizing the modified reinforcing agent; the waterproof effect of the hot melt film is improved by synthesizing the self-made water blocking agent; by controlling the preparation parameters of the modified silane coupling agent and the use amount of the improved phenolic resin, the ultraviolet resistance of the hot melt film is improved; the heat resistance of the hot melt film is improved by controlling and improving the preparation parameters of the phenolic resin and the mixing process parameters; the elongation of the hot melt film is improved by controlling the dosage of each component in the composite antioxidant and the temperature of an extruder and a cooling roller.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, in particular to a water-blocking hot-melt film of a waterproof coiled material and a preparation method thereof. Background Art

[0002] In today's construction industry, waterproofing membrane is a flexible building material product that can be rolled into a roll. It is mainly used in building walls, roofs, tunnels, roads, etc., and plays a role in resisting external rainwater and groundwater leakage. When the current waterproofing membrane is exposed for a long time, the mineral particles on the surface are easy to fall off and age, resulting in a large number of cracks or cracks on the surface of the waterproof layer, which seriously affects the waterproof effect and service life of the waterproofing membrane. On the other hand, under long-term exposure to the sun, the aging speed of the waterproofing membrane is accelerated, which to a certain extent also leads to a reduction in service life; during storage, it is also easy to be eroded by air and moisture, resulting in a weakened final waterproofing effect and a reduced service life of the waterproofing membrane.

[0003] Nowadays, many people use the measure of attaching protective film on waterproofing membrane to improve the waterproofing property of waterproofing membrane. This method can isolate the waterproofing membrane from air and moisture, and achieve the effect of increasing the service life of waterproofing membrane. However, the waterproofing property and strength of the protective film itself are also very important, which is closely related to the service life of waterproofing membrane.

[0004] In summary, the hot melt film of the current waterproof roll still has problems such as weak tensile strength and poor waterproof effect, resulting in a short service life of the waterproof roll. To this end, a water-blocking hot melt film of a waterproof roll and a preparation method thereof are proposed. Summary of the invention

[0005] The purpose of the present invention is to design a water-blocking hot-melt film for waterproof coiled material and a preparation method thereof. The synthetic raw materials of the water-blocking hot-melt film include polyolefin elastomer POE, homemade water-blocking agent, modified reinforcing agent, modified silane coupling agent, modified phenolic resin and composite antioxidant. The present invention improves the tensile strength of the hot-melt film by controlling the dosage of polyolefin elastomer POE and modified reinforcing agent and the preparation parameters of the modified reinforcing agent; improves the waterproof effect of the hot-melt film by controlling the preparation parameters and dosage of the homemade water-blocking agent and the dosage of the modified silane coupling agent; improves the anti-ultraviolet ability of the hot-melt film by changing the preparation parameters of the modified silane coupling agent and the dosage of the modified phenolic resin; improves the heat resistance of the hot-melt film by controlling the preparation parameters of the modified phenolic resin, the dosage of the composite antioxidant and the mixing process parameters; and improves the elongation of the hot-melt film by controlling the dosage of each component in the composite antioxidant and the temperature of the extruder and the cooling roller.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] In one aspect, the present invention provides a water-blocking hot-melt film for a waterproof roll material, wherein the raw materials of the water-blocking hot-melt film include the following components:

[0008] Polyolefin elastomer POE: 62-68 parts;

[0009] Homemade water-blocking agent: 6-10 parts;

[0010] Modifying enhancer: 2-5 parts;

[0011] Modified silane coupling agent: 3-6 parts;

[0012] Modified phenolic resin: 1-3 parts;

[0013] Composite antioxidant: 0.6-0.9 parts.

[0014] Preferably, the polyolefin elastomer POE is copolymerized by octene and polyolefin resin.

[0015] Preferably, the composite antioxidant is a mixture of 21-25 parts of 245 phenolic antioxidant, 3-6 parts of 9228 phosphorus antioxidant and 2-4 parts of DLTP sulfur antioxidant.

[0016] Another aspect of the present invention provides a method for preparing a water-blocking hot-melt film of a waterproof coiled material, the method for preparing the water-blocking hot-melt film comprising the following steps:

[0017] S1: 62-68 parts of polyolefin elastomer POE, 6-10 parts of homemade water-blocking agent, 2-5 parts of modified reinforcing agent, 3-6 parts of modified silane coupling agent, 1-3 parts of modified phenolic resin and 0.6-0.9 parts of composite antioxidant are put into a high-speed mixer and mixed at a temperature of TE1 at a speed of 1100 rpm-1250 rpm for 15 min-19 min to obtain a mixture A;

[0018] S2: putting the mixture A into an extruder, extruding it at a temperature TE2, casting it into a film, controlling the temperature of the cooling roller to be 5°C-15°C, and obtaining the water-blocking hot-melt film of the waterproof coiled material after extrusion and shaping.

[0019] Preferably, the preparation method of the homemade water-blocking agent described in S1 is: add 22-28 parts of perfluorooxyheteroamido quaternary ammonium salt and 1-7 parts of hydrofluoric acid to 100 parts of isopropanol, stir at room temperature for 5 hours to obtain a mixture A; add 50-80 parts of tetrahydrofuran to the mixture A, stir for 18h-24h, and remove the solvent to obtain the homemade water-blocking agent.

[0020] Preferably, the preparation method of the modified enhancer in S1 is: 12-15 parts of polyethylene and 5-8 parts of polypropylene are mixed to obtain a mixture B; 1-3 parts of sodium peroxide are added to the mixture B, and after stirring for 1 hour, the mixture is transferred to a hydrothermal reactor, reacted at 120°C-150°C for 8 hours, and centrifugally dried after the reaction to obtain the modified enhancer.

[0021] Preferably, the preparation method of the modified silane coupling agent described in S1 is: put 10-13 parts of methyltriethoxysilane and 2-4 parts of γ-aminopropyltriethoxysilane into 15 parts of N,N-dimethylformamide, stir at 60°C-80°C for 14h-29h, wash with anhydrous ethanol and dry to obtain the modified silane coupling agent.

[0022] Preferably, the preparation method of the improved phenolic resin in S1 is: add 8-12 parts of terpene phenolic resin and 8 parts of xylene modified phenolic resin to 10 parts of N,N-dimethylformamide, stir evenly to obtain a mixture C; add 6 parts of propylene glycol to the mixture C and stir, and mix evenly to obtain a mixture D; transfer the mixture D to a hydrothermal reactor for cross-linking reaction at 100°C-115°C for 6 hours, cool, wash and dry to obtain the improved phenolic resin.

[0023] Preferably, the temperature TE1 in S1 is 255°C-275°C.

[0024] Preferably, the temperature TE2 in S2 is 200°C-215°C.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1. The present invention improves the tensile strength of the hot melt film by controlling the dosage of polyolefin elastomer POE and modifier and enhancer as well as the preparation parameters of the modifier and enhancer. Polyolefin elastomer POE is selected as the base material of the hot melt film because it can maintain stable physical properties after long-term exposure to outdoor environment and its molecular structure has high compactness; polyethylene may be brittle in low temperature environment, and copolymerization of polyethylene and polypropylene can effectively improve the tensile strength of the substance; excessively high temperature during the reaction will lead to the breakage of polyethylene and polypropylene molecular chains, thereby affecting the performance of the modifier and enhancer, and ultimately reducing the tensile strength of the hot melt film; excessively low temperature will lead to the inability to fully carry out the polymerization reaction of polyethylene and polypropylene, affecting the tensile strength of the hot melt film and reducing the service life of the waterproof membrane. The final tensile strength of the hot melt film is 45.3MPa.

[0027] 2. The present invention improves the waterproof effect of the hot melt film by controlling the preparation parameters and dosage of the homemade water-blocking agent and the dosage of the modified silane coupling agent. The waterproof effect of the hot melt film is very important and will directly affect the service life of the waterproof membrane. Perfluorooxyheteroamido quaternary ammonium salt itself has excellent waterproof effect. Hydrofluoric acid is introduced into the organic solvent to catalyze the perfluorooxyheteroamido quaternary ammonium salt so that it can react with hydroxyl groups. Then tetrahydrofuran is added to dissolve the water-blocking component of the perfluorooxyheteroamido quaternary ammonium salt in tetrahydrofuran. The organic solvent is removed to obtain a homemade water-blocking agent. If the homemade water-blocking agent is used in too much amount, the flexibility of the hot melt film may deteriorate, and it may become too hardened or brittle. If the amount is too little, the waterproof effect is poor, and water seepage is likely to occur, which will affect the service life of the waterproof membrane. The modified silane coupling agent can enhance the bonding force between the hot melt membrane and the waterproof membrane. If the amount is too little, the bonding strength is insufficient and the waterproof effect is affected. If the amount is too much, the cross-linking reaction of the internal materials of the hot melt membrane will be excessive, resulting in a decrease in the toughness of the hot melt membrane, thereby affecting the waterproof effect of the hot melt membrane. The final water vapor permeability of the hot melt membrane is 23.1g / (m 2 ·24h).

[0028] 3. The present invention improves the anti-ultraviolet ability of the hot melt film by changing the preparation parameters of the modified silane coupling agent and the dosage of the modified phenolic resin. The γ-aminopropyltriethoxysilane in the modified silane coupling agent has a strong binding force. By modifying it with methyltriethoxysilane, the performance of the modified coupling agent can be improved, so that the modified phenolic resin is closely combined with other components, thereby improving the anti-ultraviolet ability of the hot melt film; terpene phenolic resin has good anti-ultraviolet ability. Introducing it into the modified phenolic resin and controlling the dosage of the modified phenolic resin can effectively improve the anti-ultraviolet ability of the hot melt film, but excessive dosage will cause the hot melt film to become brittle and easy to age, reducing the anti-ultraviolet ability, and at the same time, the bonding force becomes stronger, which is not easy to construct. Too little dosage will cause the hot melt film to become more fragile, and long-term exposure to ultraviolet rays will cause aging, which will reduce the service life of the waterproof membrane. The peel strength of the hot melt film after the final UV treatment is 3.7N / mm.

[0029] 4. The present invention improves the heat resistance of the hot melt film by controlling the preparation parameters of the modified phenolic resin, the amount of the composite antioxidant, and the mixing process parameters. The terpene phenolic resin and the xylene modified phenolic resin are cross-linked and the reaction temperature is controlled. If the reaction temperature is too high, it will lead to excessive cross-linking and molecular chain breakage, thereby reducing the performance of the modified phenolic resin and making it easy to crack under high temperature environment, affecting the heat resistance of the hot melt film. If the reaction temperature is too low, the cross-linking reaction will not be complete and the molecular chain connection will not be tight enough, thereby reducing the heat resistance of the hot melt film. If the amount of composite antioxidant is too much, the hot melt film will become rigid, thereby affecting the service life of the waterproof coiled material. If the amount is too little, the aging speed of the hot melt film will be accelerated, and the service life of the waterproof coiled material will be reduced. The control of process parameters in the high-speed mixer will also affect the heat resistance of the hot melt film. If the temperature is too high, thermal degradation will occur, resulting in the volatilization of some components, thereby affecting the service life of the waterproof coiled material. Finally, the hot melt film has no displacement at high temperature.

[0030] 5. The present invention improves the elongation of the hot melt film by controlling the dosage of each component in the composite antioxidant and the temperature of the extruder and the cooling roller. The antioxidant performance of the composite antioxidant is improved by mixing various types of antioxidants in different dosages, so that the hot melt film is not prone to aging and the elongation of the hot melt film is improved; if the temperature of the extruder is too high, some components will be thermally decomposed, and the thickness structure will be uneven, which will affect the elongation of the hot melt film. If the temperature is too low, the fluidity of the material is poor and the viscosity is too high, which may cause the extruder to be blocked; if the temperature of the cooling roller is too high, the hot melt film fails to cool down quickly when passing through the cooling roller, which may cause wrinkles and bubbles on the surface of the hot melt film, and the surface of the hot melt film will become soft and may adhere to the roller surface, causing the film surface to be damaged or not smooth, thereby affecting the elongation of the hot melt film. If the temperature of the cooling roller is too low, the surface of the hot melt film has solidified, but the internal temperature is still very high, which may cause bubbles to be generated inside the hot melt film, thereby affecting the waterproof effect and elongation of the hot melt film, making the hot melt film easy to crack and reducing the service life of the waterproof coiled material. The final hot-melt film has a longitudinal elongation of 89% and a transverse elongation of 95%. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a graph of water vapor transmission rates of Example 17, Examples 21-22, Examples 24-26, Examples 28-32, Examples 34-35 and Comparative Examples 2-3 of the present invention. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Specific reference Figure 1 The present invention provides a water-blocking hot-melt film of a waterproof coiled material and a preparation method thereof, and the technical scheme is as follows:

[0034] Example 1

[0035] Preparation of homemade water blocking agent:

[0036] 22 parts of perfluorooxoamido quaternary ammonium salt and 1 part of hydrofluoric acid were added to 100 parts of isopropanol, and stirred at room temperature for 5 hours to obtain a mixture A; 50 parts of tetrahydrofuran were added to the mixture A, and stirred for 18 hours. After removing the solvent, the self-made water-blocking agent was obtained.

[0037] Preparation of modified reinforcing agent:

[0038] 12 parts of polyethylene and 5 parts of polypropylene are mixed to obtain a mixture B; 1 part of sodium peroxide is added to the mixture B, and the mixture is transferred to a hydrothermal reactor after stirring for 1 hour, and reacted at 120° C. for 8 hours. After the reaction is completed, centrifugal drying is performed to obtain the modified enhancer.

[0039] Preparation of modified silane coupling agent:

[0040] 10 parts of methyltriethoxysilane and 2 parts of γ-aminopropyltriethoxysilane were put into 15 parts of N,N-dimethylformamide, stirred at 60° C. for 14 hours, washed with anhydrous ethanol and dried to obtain the modified silane coupling agent.

[0041] Preparation of modified phenolic resin:

[0042] 8 parts of terpene phenolic resin and 8 parts of xylene modified phenolic resin are added to 10 parts of N,N-dimethylformamide, and stirred to obtain a mixture C; 6 parts of propylene glycol are added to the mixture C and stirred to obtain a mixture D after mixing evenly; the mixture D is transferred to a hydrothermal reactor for cross-linking reaction at 100° C. for 6 hours, and then washed and dried after cooling to obtain the modified phenolic resin.

[0043] The composite antioxidant is prepared by mixing 21 parts of 245 phenolic antioxidant, 3 parts of 9228 phosphorus antioxidant and 2 parts of DLTP sulfur antioxidant.

[0044] Preparation of water-blocking hot-melt film:

[0045] S1: 62 parts of polyolefin elastomer POE, 6 parts of homemade water-blocking agent, 2 parts of modified reinforcing agent, 3 parts of modified silane coupling agent, 1 part of modified phenolic resin and 0.6 parts of composite antioxidant were put into a high-speed mixer and mixed at 255° C. and 1100 rpm for 15 min to obtain mixture A;

[0046] S2: putting the mixture A into an extruder, extruding it at 200° C., casting it into a film, controlling the temperature of the cooling roller to be 5° C., and obtaining the water-blocking hot-melt film of the waterproof coiled material after extrusion and shaping.

[0047] Example 2-18

[0048] Referring to the parameter conditions of the preparation method in Example 1, the specific differences are shown in Table 1.

[0049] Table 1 Parameter conditions of Examples 1-18

[0050]

[0051]

[0052] Comparative Example 1

[0053] The parameters and conditions of the preparation method in Example 1 are referred to, except that no modifying enhancer is added.

[0054] Example 19 Tensile Strength Test

[0055] By stretching Examples 1-18 and Comparative Example 1 until they break, recording the applied force and the deformation of the sample, the tensile strength of Examples 1-18 and Comparative Example 1 was finally calculated. The calculation formula is: σ(tensile strength / MPa)=F / A, where F is the maximum tensile force that the sample withstands during the stretching process, and A is the initial cross-sectional area of ​​the sample. The results are shown in Table 2.

[0056] Table 2 Tensile strength test of Examples 1-18 and Comparative Example 1

[0057]

[0058]

[0059] It can be found from Table 2 that in Comparative Example 1, no modifier was added, and its tensile strength was only 25.8MPa, which was much lower than that of other examples, indicating that the modifier can significantly improve the tensile strength of the hot melt film, thereby improving the life of the waterproof roll. In Examples 1-18, when the amount of polyolefin elastomer POE was changed, and the preparation parameters and amount of the modifier remained unchanged, the tensile strength of the hot melt film first increased and then decreased. When the amount of polyolefin elastomer POE was 66 parts, the tensile strength was the largest. The tensile strength of Example 3 was 37.2MPa, because polyolefin elastomer POE was selected as the base material of the hot melt film, because it can still maintain stable physical properties under long-term exposure to outdoor environments, and the molecular structure has a high compactness; when the polyolefin elastomer POE was fixed, the tensile strength of the hot melt film increased first and then decreased. The dosage of OE is 66 parts. When the dosage of polyethylene, polypropylene and sodium peroxide is changed, the tensile strength is the highest when the dosage of polyethylene is 14 parts, the dosage of polypropylene is 6 parts, and the dosage of sodium peroxide is 2 parts. The tensile strength of Example 11 is 42.3MPa. Because polyethylene may be brittle in a low temperature environment, copolymerization of polyethylene and polypropylene can effectively improve the tensile strength of the substance; when the dosage of polyolefin elastomer POE is 66 parts, the dosage of polyethylene is 14 parts, the dosage of polypropylene is 6 parts, and the dosage of sodium peroxide is 2 parts, the tensile strength of Example 11 is 42.3MPa. The amount of sodium used is 2 parts. When the reaction temperature is changed, the higher the reaction temperature, the greater the tensile strength. When it exceeds 130°C, the tensile strength decreases. The tensile strength of Example 13 is the largest, which is 43.5MPa. Because the temperature is too high during the reaction process, the polyethylene and polypropylene molecular chains will break, thereby affecting the performance of the modified enhancer and ultimately reducing the tensile strength of the hot-melt film. Too low a temperature will cause the polymerization reaction of polyethylene and polypropylene to be unable to proceed fully, affecting the tensile strength of the hot-melt film and reducing the service life of the waterproof membrane. When the polyolefin The amount of hydrocarbon elastomer POE is 66 parts, the amount of polyethylene is 14 parts, the amount of polypropylene is 6 parts, the amount of sodium peroxide is 2 parts, and the reaction temperature is 130°C. When the amount of the modifying enhancer is changed, the tensile strength is the largest when the amount of the modifying enhancer is 4 parts. The tensile strength of Example 17 is 45.3MPa. This is because excessive use of the modifying enhancer will cause the hot-melt film to be too hard and brittle, and lose the necessary flexibility, which is not conducive to subsequent use. Too little use will cause the hot-melt film to have insufficient tensile strength, affecting the service life of the waterproof membrane.

[0060] Examples 20-35

[0061] Referring to the parameter conditions of the preparation method in Example 17, the difference is that the preparation parameters and dosage of the homemade water-blocking agent and the dosage of the modified silane coupling agent are changed. The specific differences are shown in Table 3.

[0062] Table 3 Parameter conditions of Example 17 and Examples 20-35

[0063]

[0064] Comparative Example 2

[0065] The parameters and conditions of the preparation method in Example 17 are referred to, except that no homemade water-blocking agent is added.

[0066] Comparative Example 3

[0067] The parameters and conditions of the preparation method in Example 17 are referred to, except that no modified silane coupling agent is added.

[0068] Example 36 Waterproof Effect Test

[0069] According to the standard GB / T 1037-2021, the water vapor permeability test was performed on Example 17, Examples 20-35 and Comparative Examples 2-3 to detect the waterproof effect of the hot melt film. The results are shown in Table 4. The water vapor permeability of Example 17, Examples 21-22, Examples 24-26, Examples 28-32, Examples 34-35 and Comparative Examples 2-3 is shown in Table 4. Figure 1 shown.

[0070] Table 4 Waterproof effect test of Example 17, Examples 20-35 and Comparative Examples 2-3

[0071] Example <![CDATA[Water vapor transmission rate / g / (m 2 ·24 h)]]> Embodiment 17 29.0 Embodiment 20 28.4 Embodiment 21 27.6 Embodiment 22 28.1 Embodiment 23 27.0 Embodiment 24 26.4 Embodiment 25 27.1 Embodiment 26 25.8 Embodiment 27 26.2 Embodiment 28 26.9 Embodiment 29 25.0 Embodiment 30 25.6 Embodiment 31 24.2 Embodiment 32 24.8 Embodiment 33 23.6 Embodiment 34 23.1 Embodiment 35 23.5 Comparative Example 2 51.3 Comparative Example 3 32.8

[0072] From Table 4 and Figure 1 It can be found that in Comparative Example 2, no homemade water-blocking agent was added, and the waterproof performance of Comparative Example 2 was poor, with a water vapor transmission rate of 51.3 g / (m 2 ·24h), which is much higher than other embodiments, and will seriously affect the service life of the waterproof coiled material; in Comparative Example 3, no modified silane coupling agent was added, and the waterproof effect of Comparative Example 3 was also poor, indicating that the components cannot be tightly connected and will also affect the waterproof effect of the hot melt film. In Examples 17 and Examples 20-35, when the amount of perfluorooxyheteroamido quaternary ammonium salt was changed and other parameters remained unchanged, the waterproof effect was first enhanced and then decreased. When the amount of perfluorooxyheteroamido quaternary ammonium salt was 26 parts, Example 21 had the best waterproof effect, and the water vapor transmission rate was 27.6g / (m 2 ·24h); when the dosage of perfluorooxaamino quaternary ammonium salt is 26 parts, the dosage of hydrofluoric acid and tetrahydrofuran is changed, and other parameters remain unchanged, the waterproof effect is best when the dosage of hydrofluoric acid is 5 parts and the dosage of tetrahydrofuran is 60 parts, and the water vapor permeability of Example 26 is 25.8g / (m 2·24h); when the amount of perfluorooxaamido quaternary ammonium salt is 26 parts, the amount of hydrofluoric acid is 5 parts, and the amount of tetrahydrofuran is 60 parts, the stirring time is changed, and other parameters remain unchanged. The longer the stirring time, the better the waterproof effect. When the stirring time exceeds 21h, the waterproof effect gradually deteriorates. At this time, the waterproof effect of Example 29 is the best, and the water vapor transmission rate is 25.0g / (m 2 ·24h), because the perfluorooxaamido quaternary ammonium salt itself has an excellent waterproof effect, an appropriate amount of hydrofluoric acid is introduced into the organic solvent to catalyze the perfluorooxaamido quaternary ammonium salt so that it can react with hydroxyl groups, and then tetrahydrofuran is added to dissolve the water-blocking component of the perfluorooxaamido quaternary ammonium salt in tetrahydrofuran, and the organic solvent is removed to obtain a homemade water-blocking agent, which can effectively improve the waterproof effect of the hot-melt film, thereby extending the service life of the waterproof membrane; when the amount of perfluorooxaamido quaternary ammonium salt is 26 parts, the amount of hydrofluoric acid is 5 parts, the amount of tetrahydrofuran is 60 parts, and the stirring time is 21h, the amount of the homemade water-blocking agent is changed, and other parameter conditions remain unchanged, the waterproof effect is best when the amount of the homemade water-blocking agent is 8 parts, and the water vapor permeability of Example 31 is 24.2g / (m 2 ·24h), because if the amount of the homemade water-blocking agent is too much, the flexibility of the hot-melt film may be reduced, becoming too hardened or brittle, and if the amount is too little, the waterproof effect will be poor, and water seepage will easily occur, which will affect the service life of the waterproof membrane; when other parameter conditions are fixed and the amount of the modified silane coupling agent is changed, the waterproof effect is first enhanced and then weakened. When the amount of the modified silane coupling agent is 5, the water vapor permeability of Example 34 is 23.1g / (m 2 ·24h), the waterproof effect is the best at this time, because the modified silane coupling agent can enhance the bonding strength between the hot melt film and the waterproof membrane. Too little dosage will lead to insufficient bonding strength and affect the waterproof effect. Too much dosage will lead to excessive cross-linking reaction of the internal materials of the hot melt film, resulting in a decrease in the toughness of the hot melt film, thereby affecting the waterproof effect of the hot melt film and reducing the service life of the waterproof membrane.

[0073] Examples 37-48

[0074] Referring to the parameter conditions of the preparation method in Example 34, the difference lies in that the preparation parameters of the modified silane coupling agent and the amount of the modified phenolic resin are changed. The specific differences are shown in Table 5.

[0075] Table 5 Parameters and conditions of Example 34 and Examples 37-48

[0076]

[0077]

[0078] Comparative Example 4

[0079] The parameters and conditions of the preparation method in Example 34 are the same, except that no modified phenolic resin is added.

[0080] Example 49 UV resistance test

[0081] According to the standard GB / T 23457-2009, the peel strength of Example 34, Examples 37-48 and Comparative Example 4 after UV treatment was tested to observe their anti-UV ability. The results are shown in Table 6.

[0082] Table 6 Anti-ultraviolet ability test of Example 34, Examples 37-48 and Comparative Example 4

[0083] Example Peel strength after UV treatment / N / mm Embodiment 34 1.7 Embodiment 37 1.9 Embodiment 38 2.3 Embodiment 39 2.0 Embodiment 40 2.7 Embodiment 41 2.4 Embodiment 42 3.1 Embodiment 43 2.8 Embodiment 44 3.4 Embodiment 45 3.0 Embodiment 46 2.8 Embodiment 47 3.7 Embodiment 48 3.2 Comparative Example 4 1.5

[0084] It can be found from Table 6 that in Comparative Example 4, no modified phenolic resin was added, and the peel strength of the hot melt film after UV treatment was significantly lower than that of other embodiments, and the peel strength was 1.5 N / mm, indicating that the modified phenolic resin can effectively improve the anti-ultraviolet ability of the hot melt film. In Examples 34 and 37-48, when the amount of methyltriethoxysilane was changed and other parameters remained unchanged, the peel strength of the hot melt film after UV treatment was the largest when the amount of methyltriethoxysilane was 12 parts, and the peel strength of Example 38 was 2.3 N / mm; when the amount of methyltriethoxysilane was 12 parts, the amount of γ-aminopropyltriethoxysilane was changed, and other parameters remained unchanged, the peel strength of the hot melt film after UV treatment was the largest when the amount of γ-aminopropyltriethoxysilane was 12 parts. When the amount of oxysilane is 3 parts, the peel strength of Example 40 is the largest, and the peel strength of Example 40 is 2.7N / mm. This is because the γ-aminopropyltriethoxysilane in the modified silane coupling agent has a strong binding force. By modifying it with methyltriethoxysilane, the performance of the modified coupling agent can be improved, so that the modified phenolic resin is closely combined with other components, thereby improving the anti-ultraviolet ability of the hot melt film; when the amount of methyltriethoxysilane is 12 parts and the amount of γ-aminopropyltriethoxysilane is 3 parts, the modified When the stirring temperature and time are changed and other parameters remain unchanged, the stirring temperature is 70°C and the time is 19h. The peel strength of Example 44 is the largest, which is 3.4N / mm. This is because the stirring temperature and time will affect the composite strength of methyltriethoxysilane and γ-aminopropyltriethoxysilane, so that the modified silane coupling agent can achieve the optimal performance, thereby improving the anti-ultraviolet ability of the hot melt film. When other parameters are fixed and the amount of modified phenolic resin is changed, the peel strength of the hot melt film after UV treatment first increases and then decreases. When the amount of modified phenolic resin is 2 parts, the peel strength of the hot melt film after UV treatment is the largest. The peel strength of Example 47 is 3.7N / mm. This is because excessive use of modified phenolic resin will cause the hot melt film to become brittle and easy to age, which reduces the anti-ultraviolet ability. At the same time, the bonding force becomes stronger and it is not easy to construct. Too little use will cause the hot melt film to become more fragile, and long-term exposure to ultraviolet rays will cause aging, which will reduce the service life of the waterproof membrane.

[0085] Examples 50-64

[0086] Referring to the parameter conditions of the preparation method in Example 47, the difference lies in that the preparation parameters of the modified phenolic resin, the amount of the composite antioxidant and the mixing process parameters are changed. The specific differences are shown in Table 7.

[0087] Table 7 Parameters and conditions of Example 47 and Examples 50-64

[0088]

[0089]

[0090] Comparative Example 5

[0091] Refer to the parameter conditions of the preparation method in Example 47, except that no composite antioxidant is added.

[0092] Comparative Example 6

[0093] Refer to the parameter conditions of the preparation method in Example 47, except that the mixing temperature TE1 is 350°C, the rotation speed is 2000 rpm, and the time is 1 hour.

[0094] Comparative Example 7

[0095] Refer to the parameter conditions of the preparation method in Example 47, except that the mixing temperature TE1 is 150°C, the rotation speed is 500 rpm, and the time is 5 min.

[0096] Example 65 Heat resistance test

[0097] The heat resistance of Example 47, Examples 50-64 and Comparative Examples 5-7 was tested according to the test method in standard GB / T 328.11-2007. The results are shown in Table 8.

[0098] Table 8 Heat resistance test of Example 47, Examples 50-64 and Comparative Examples 5-7

[0099]

[0100]

[0101] It can be found from Table 8 that in Comparative Example 5, no composite antioxidant was added. At this time, the heat resistance of the hot melt film was poor, dripping occurred, and it was difficult to protect the waterproof membrane, affecting the service life of the waterproof membrane; the heat resistance of Comparative Example 6 was also poor, because if the mixing temperature was too high, thermal degradation would occur, causing volatilization of some components, thereby affecting the service life of the waterproof membrane, and if the rotation speed was too fast, air would be brought into the mixture, generating a large number of bubbles, thereby affecting the uniformity of the mixture, and if the time was too long, the shear force in the high-speed mixer would be too large, which might cause the molecular chains of some polymer materials to break, thereby affecting the heat resistance of the hot melt film; in Comparative Example 7, the hot melt film also had dripping, because if the mixing temperature was too low, the various components would be mixed unevenly, thereby affecting the overall performance, if the rotation speed was too slow, the mixture might adhere to the mixer, increasing the difficulty of implementation, and if the time was too short, the various components would be mixed unevenly, affecting the performance of the hot melt film. In Example 47 and Examples 50-64, when the amount of terpene phenolic resin and the reaction temperature are changed, and other parameter conditions remain unchanged, the heat resistance of the hot melt film is best when the amount of terpene phenolic resin is 10 parts and the reaction temperature is 110°C. The terpene phenolic resin and the xylene modified phenolic resin are cross-linked and the reaction temperature is controlled. If the reaction temperature is too high, excessive cross-linking will occur, and the molecular chain will break, thereby reducing the performance of the modified phenolic resin, which is easy to crack under high temperature environment, affecting the heat resistance of the hot melt film. If the reaction temperature is too low, the cross-linking reaction will not be complete, and the connection of the molecular chain is not tight enough, thereby reducing the heat resistance of the hot melt film. When the amount of terpene phenolic resin is 10 parts, the reaction temperature is 110°C, the dosage of the composite antioxidant is changed, and when other parameter conditions remain unchanged, the dosage of the composite antibacterial agent is 0.8 parts, the heat resistance of the hot melt film is the best, and Example 56 is in a flowing state, because excessive dosage of the composite antioxidant will cause the hot melt film to become rigid, thereby affecting the service life of the waterproof membrane, and too little dosage will cause the aging speed of the hot melt film to accelerate, and the service life of the waterproof membrane will be reduced; when other parameter conditions are fixed, the process parameters of the high-speed mixer are changed, and Example 63 has the best heat resistance and is in a non-displacement state, because maintaining appropriate process parameters is conducive to uniform mixing of the components and achieving the optimal effect, thereby improving the heat resistance of the hot melt film and extending the service life of the waterproof membrane.

[0102] Examples 66-77

[0103] Referring to the parameter conditions of the preparation method in Example 63, the difference is that the amount of each component in the composite antibacterial agent and the temperature of the extruder and the cooling roller are changed. The specific differences are shown in Table 9.

[0104] Table 9 Parameters and conditions of Example 63 and Examples 66-77

[0105]

[0106] Comparative Example 8

[0107] Refer to the parameter conditions of the preparation method in Example 63, except that the temperature TE2 of the extruder is 300°C and the temperature of the cooling roller is 60°C.

[0108] Comparative Example 9

[0109] Refer to the parameter conditions of the preparation method in Example 63, except that the temperature TE2 of the extruder is 100°C and the temperature of the cooling roller is -10°C.

[0110] Example 78 Elongation Test

[0111] According to GB 18242-2000 standard, the longitudinal and transverse elongation of Example 63, Examples 66-77 and Comparative Examples 8-9 were tested, and the results are shown in Table 10.

[0112] Table 10 Elongation test of Example 63, Examples 66-77 and Comparative Examples 8-9

[0113] Example Longitudinal elongation / % Transverse elongation / % Embodiment 63 73 77 Embodiment 66 75 80 Embodiment 67 72 76 Embodiment 68 77 83 Embodiment 69 74 81 Embodiment 70 72 78 Embodiment 71 79 87 Embodiment 72 76 84 Embodiment 73 82 90 Embodiment 74 86 93 Embodiment 75 84 91 Embodiment 76 89 95 Embodiment 77 85 92 Comparative Example 8 59 65 Comparative Example 9 62 66

[0114] It can be found from Table 10 that in Comparative Example 8, the temperature of the extruder and the cooling roller is too high, which will lead to a decrease in the elongation of the hot melt film, because the temperature of the extruder is too high, which will cause thermal decomposition of certain components and uneven thickness structure, affecting the elongation of the hot melt film. When the temperature of the cooling roller is too high, the hot melt film fails to cool down quickly when passing through the cooling roller, which may cause wrinkles and bubbles on the surface of the hot melt film, and also soften the surface of the hot melt film, which may adhere to the surface of the roller, causing the film surface to be damaged or not smooth, affecting the elongation; in Comparative Example 9, the temperature of the extruder and the cooling roller is too low, which will also lead to poor elongation of the hot melt film, because when the temperature of the extruder is too low, the fluidity of the material is poor, and the viscosity is too high, which may cause the extruder to be blocked. When the temperature of the cooling roller is too low, the surface of the hot melt film has solidified, but the internal temperature is still very high, which may cause bubbles to form inside the hot melt film, thereby affecting the waterproof effect and elongation of the hot melt film, making the hot melt film easy to crack, and reducing the service life of the waterproof membrane. When the dosage of each component in the composite antibacterial agent is changed and other parameter conditions remain unchanged, the longitudinal and transverse elongation of the hot melt film reaches the highest when the dosage of 245 phenolic antioxidant is 23 parts, the dosage of 9228 phosphorus antibacterial agent is 4 parts, and the dosage of DLTP sulfur antibacterial agent is 3 parts. At this time, the longitudinal elongation of Example 71 is 79%, and the transverse elongation is 87%. The various types of antioxidants are mixed in different dosages to improve the antioxidant properties of the composite antioxidant, so that the hot melt film is not prone to aging, and the elongation of the hot melt film is improved; when other parameter conditions are fixed and the temperature of the extruder and the cooling roller is changed, the longitudinal and transverse elongation of the hot melt film reaches the highest when the temperature of the extruder is 210°C and the temperature of the cooling roller is 10°C. The longitudinal elongation of Example 76 is 89%, and the transverse elongation is 95%. Because keeping the extruder and the cooling roller at a suitable temperature is conducive to the casting and molding of the hot melt film, thereby ensuring that the hot melt film has a good elongation and is not easy to crack, thereby improving the service life of the waterproof membrane.

[0115] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A water-blocking hot-melt film for waterproof coiled material, characterized in that: The raw materials of the water-blocking hot-melt film include the following components: Polyolefin elastomer POE: 62-68 parts; Homemade water-blocking agent: 6-10 parts; Modifying enhancer: 2-5 parts; Modified silane coupling agent: 3-6 parts; Modified phenolic resin: 1-3 parts; Composite antioxidant: 0.6-0.9 parts.

2. The water-blocking hot-melt film of a waterproof coiled material according to claim 1, characterized in that: The polyolefin elastomer POE is copolymerized with octene and polyolefin resin.

3. The water-blocking hot-melt film of a waterproof roll material according to claim 1, characterized in that: The composite antioxidant is prepared by mixing 21-25 parts of 245 phenol antioxidant, 3-6 parts of 9228 phosphorus antioxidant and 2-4 parts of DLTP sulfur antioxidant.

4. A method for preparing a water-blocking hot-melt film for a waterproof coiled material, characterized in that: The water-blocking hot-melt film according to claim 1 is prepared, and the preparation method comprises the following steps: S1: 62-68 parts of polyolefin elastomer POE, 6-10 parts of homemade water-blocking agent, 2-5 parts of modified reinforcing agent, 3-6 parts of modified silane coupling agent, 1-3 parts of modified phenolic resin and 0.6-0.9 parts of composite antioxidant are put into a high-speed mixer and mixed at a temperature of TE1 at a speed of 1100 rpm-1250 rpm for 15 min-19 min to obtain a mixture A; S2: putting the mixture A into an extruder, extruding it at a temperature TE2, casting it into a film, controlling the temperature of the cooling roller to be 5°C-15°C, and obtaining the water-blocking hot-melt film of the waterproof coiled material after extrusion and shaping.

5. The method for preparing a water-blocking hot-melt film for a waterproof coiled material according to claim 4, characterized in that: The preparation method of the homemade water-blocking agent described in S1 is: add 22-28 parts of perfluorooxyheteroamido quaternary ammonium salt and 1-7 parts of hydrofluoric acid to 100 parts of isopropanol, stir at room temperature for 5 hours to obtain a mixture A; add 50-80 parts of tetrahydrofuran to the mixture A, stir for 18h-24h, and remove the solvent to obtain the homemade water-blocking agent.

6. The method for preparing a water-blocking hot-melt film for a waterproof coiled material according to claim 4, characterized in that: The preparation method of the modified enhancer described in S1 is: 12-15 parts of polyethylene and 5-8 parts of polypropylene are mixed to obtain a mixture B; 1-3 parts of sodium peroxide are added to the mixture B, and after stirring for 1 hour, the mixture is transferred to a hydrothermal reactor, reacted at 120°C-150°C for 8 hours, and centrifugally dried after the reaction to obtain the modified enhancer.

7. The method for preparing a water-blocking hot-melt film for a waterproof coiled material according to claim 4, characterized in that: The preparation method of the modified silane coupling agent described in S1 is: put 10-13 parts of methyltriethoxysilane and 2-4 parts of γ-aminopropyltriethoxysilane into 15 parts of N,N-dimethylformamide, stir at 60°C-80°C for 14h-29h, wash with anhydrous ethanol and dry to obtain the modified silane coupling agent.

8. The method for preparing a water-blocking hot-melt film for a waterproof coiled material according to claim 4, characterized in that: The preparation method of the improved phenolic resin described in S1 is: add 8-12 parts of terpene phenolic resin and 8 parts of xylene modified phenolic resin to 10 parts of N, N-dimethylformamide, stir evenly to obtain a mixture C; add 6 parts of propylene glycol to the mixture C and stir, and mix evenly to obtain a mixture D; transfer the mixture D to a hydrothermal reactor for cross-linking reaction at 100°C-115°C for 6 hours, cool, wash and dry to obtain the improved phenolic resin.

9. The method for preparing a water-blocking hot-melt film for a waterproof coiled material according to claim 4, characterized in that: The temperature TE1 in S1 is 255°C-275°C.

10. The method for preparing a water-blocking hot-melt film for a waterproof coiled material according to claim 4, characterized in that: The temperature TE2 in S2 is 200°C-215°C.

Citation Information

Patent Citations

  • Hot melt adhesive film for bonding TPO waterproof coiled material and metal plate and preparation method of hot melt adhesive film

    CN111040661A

  • PE / POE (Polyethylene / Polyolefin Elastomer) composite self-adhesive film waterproof roll as well as preparation method and application thereof

    CN114907783A

  • Adhesive film applied to waterproof roll and preparation method of adhesive film

    CN116179109A

  • Hot melt film for building waterproof coiled material and production process of hot melt film

    CN118702995A

  • Thin film, base film, waterproof coiled material and use thereof

    WO2022052943A1